Phospholipase C-β1 hypofunction in the pathogenesis of schizophrenia - Kim, Seong-Wook; Cho, Taesup; Lee, Sukchan (Frontiers in Psychiatry, 2015)
Schizophrenia is a mental disorder that is characterized by various abnormal symptoms. Previous studies indicate decreased expression of phospholipase C-β1 (PLC-β1) in the brains of patients with schizophrenia. PLC-β1-null (PLC-β1−/−) mice exhibit multiple endophenotypes of schizophrenia. Furthermore, a study of PLC-β1 knockdown in the medial prefrontal cortex of mice has shown a specific behavioral deficit, impaired working memory. These results support the notion that disruption of PLC-β1-linked signaling in the brain is strongly involved in the pathogenesis of schizophrenia. In this review, we broadly investigate recent studies regarding schizophrenia-related behaviors as well as their various clinical and biological correlates in PLC-β1−/− and knockdown mouse models. This will provide a better understanding of the pathological relevance of the altered expression of PLC-β1 in the brains of patients with schizophrenia. Evidence accumulated will shed light on future in-depth studies, possibly in human subjects.